Assessing Adolescent Adaptability: Development of a New Psychological Adjustment Scale - Iram Naz; Nasia Tabassum; Shumaila Ilyas (Indus Journal of Social Sciences, 2025)
The psychological problems are problematic in every society. To address the psychological problems and for their determination the assessment tools are required. The present study assesses adolescent adaptability by developing a new psychological adjustment scale. At first, a pool of 168 items was originated through interview and searching literature. The pilot study was initially done with 162 items and after pilot study 75 items were retained that includes the dimensions of depression, anxiety and disturbance of conduct according to DSM criteria of adjustment disorders. Further, field administration of these items was done on 400 adolescents by using self-administered questionnaire. The data was examined by using exploratory and confirmatory factor analysis and reliability test. Among 75 items 20 items were found reliable at the end of analysis. The reliability of the sub-scales was between ranges of .688 to .800. Psychometric properties of psychological adjustment scale were confirmed above 100 participants. Convergent validity was determined with suicide scale for adolescents. The convergent validity showed significant correlation value of .345 establishing validity. The divergent validity showed no relationship between moral disengagement and social anxiety with psychological adjustment problems. Psychological adjustment scale for adolescents was a reliable and valid instrument for assessing psychological adjustment problems of adolescents.